2019
DOI: 10.3390/ijerph16162934
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Land Expropriation on Land-Lost Farmers’ Health: Empirical Evidence from Rural China

Abstract: With rapid urbanization and industry development, China has witnessed substantial land acquisition. Using the rural household survey data, this paper examines the impact of land expropriation on land-lost farmers’ self-reported health with the ordered probit model and investigates the possible mechanisms. The results show that the land expropriation puts higher health risks over those land-lost farmers and the health status of land-lost farmers is significantly worse than that of those with land. Land expropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…In China, land expropriation has negative impacts on the health of farmers who lost their land due to effects on income and protection for the long term (Wang et al, 2019). A study conducted on two rural counties in California indicated that mental health impacts were caused by finances and property (Barreau et al, 2017).…”
Section: Financial Hardshipmentioning
confidence: 99%
“…In China, land expropriation has negative impacts on the health of farmers who lost their land due to effects on income and protection for the long term (Wang et al, 2019). A study conducted on two rural counties in California indicated that mental health impacts were caused by finances and property (Barreau et al, 2017).…”
Section: Financial Hardshipmentioning
confidence: 99%
“…According to Guo et al [24], expropriation schemes have resulted in drastic changes in rural households' livelihoods in China. Expropriated farmers' incomes declined because of land loss, and their long-term livelihoods are jeopardized [3,23,24,28,29,39]. Apparently, the loss of farmlands has multiple negative effects on the livelihoods of these farming households [40].…”
Section: Expropriation In a National And International Contextmentioning
confidence: 99%
“…On the other hand, due to the lack of human capital and social capital stocks of land-lost farmers, they are vulnerable to functional exclusion. Therefore, land acquisition will not only have a negative impact on the welfare status of land-lost farmers, but also affect the urban adaptation status, health level, and happiness of the land-lost farmers [92]. This will provide suggestions for the local government to revise the current land use policy, increase the compensation for land acquisition, and improve the income level and mental health of land-lost farmers.…”
Section: Analysis Of Evaluation Resultsmentioning
confidence: 99%